A comparative study of different microchips for capillary electrophoresis with electrochemical detection - Erro, Eustaquio Martín (2014)
This work describes a comparison of the performance of different microchip configuration for microchip capillary electrophoresis with electrochemical detection. Two electrodes gold and multistrand carbon fibers and two microchip construction materials polydimethylsiloxane/polydimethylsiloxane (PDMS/PDMS) and polydimethylsiloxane/glass hybrid (PDMS/glass) were analyzed. The electrode is integrated into the microchip for in-channel triple pulse amperometric detection. Two different mixtures were analyzed (i.e., paracetamol (PA)-4-aminophenol (4-AP) and Dopamine (DO)-Dopac) to demonstrate the electrode and microchips performance. Other variables, such as injection and separation potentials, buffer pH, surfactants addition and injection time, were also analyzed. Hydrodynamic voltammograms were used to select working potential values, and +0.9 V for PA and 4-AP and +0.8 V for DO and dopac were chosen. The migration potential was modified in the 1,500–2,500 V range, and the employed value depends on the microchip materials. The separation process was tested by analyzing the current and migration time variation coefficients. The experimental results demonstrated that the hybrid PDMS/glass microchip with a carbon fiber electrode exhibited a better performance for both samples analyzed.